Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Turbulence-induced detachment of fine particles from bubble surfaces and associated flow field characteristics - Hailing He; Zhixin Sun; Xiaoheng Li; Xiaokang Yan; Lijun Wang; Haijun Zhang; Li Lin; Jincai Ran (Minerals Engineering, 2026)

PPIB interacts with MET to activate the PI3K-AKT pathway and promote head and neck squamous cell carcinoma pathogenesis - Zhaobo Liu; Lin Wang; Jin Tang; Jingxuan Ran; Linsheng Dong; Yadong Li (Molecular Biology Reports, 2026)

The role of macrophage-myofibroblast transition in the pathogenesis of multi-organ fibrosis - Congcong Guo; Ran Cao; Lin Liao; Junyu Zhao; Tianzuo Wang; Junhan Li; Yue Zhang; Haotian Li (Tissue and Cell, 2026)

A salivary elicitor MsPDI3 from Mythimna separata triggers plant defense responses - Jin-Da Wang; Huan-Tai Lin; Lin Li; Yao-Hui Chen; Ran Wang; Honglin Feng; San-Ji Gao (Insect Biochemistry and Molecular Biology, 2026)

Pre-transport dietary chitosan improves the physiological robustness of juvenile largemouth bass (Micropterus salmoides) by modulating antioxidant and inflammatory responses - Hong-Zheng Zhao; Yu-Lin Chang; Chang Wang; Yu-Yun He; Yi-Ran Zhao; Yi-Chen Dong; Xu-Xiong Huang; Guo-Fang Zhong (Fish & Shellfish Immunology, 2026)

Exciton regulation and directional electron transfer in artemisia-derived carbon dots/g-C3N4 heterojunction for enhanced visible-light photocatalytic antibacterial activity - Mingzhu Yuan; Weile Xie; Ran Qiu; Mingxin Zhou; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Da Fu; Xiangang Lin (Chemical Engineering Journal, 2026)

Inhibition of Sonic Hedgehog signaling pathway by GANT61 alleviates adenomyosis by suppressing epithelial-to-mesenchymal transition, cell migration and proliferation - Zaifan Lin; Simiao Yan; Qingzhen Ran; Qianxin Yang; Haixin Lin; Jingtong Sun; Yi Chen; Xiuchi Zhong; Yingzhou Tian; Wanqun Chen (Tissue and Cell, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

WTAP upregulates HK2 expression via m6A methylation to reprogram cell glycolysis and stemness under Cr(VI) exposure - Yunxia Xie; Lin Wang; Ruike Zhang; Wenwen Ran; Bing-Hua Jiang; Xiaoming Xing (Journal of Environmental Sciences, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Comparative metabolomic analysis of flavor and metabolite profiles across cultivated kiwifruit species - Ran Wang; Chengkui Qiao; Li Liu; Ziqi Zhang; Sikai Li; Miaomiao Lin; Yukuo Li; Jinbao Fang; Leiming Sun; Xiujuan Qi (Food Chemistry, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Experimental investigation on seismic performance evolution of reinforced concrete columns considering spatially differential corrosion - Yang Liu; Wei-Ping Zhang; Qian-Qian Yu; Hao-Ran Zuo; Xiang-Lin Gu (Engineering Structures, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Smartphone-assisted fluorescence and colorimetric dual-mode sensor for visual quantitative detection of nitrite and nitrate in real samples - Fei Lin; Jie Cao; Yingying Liu; Xuelian Zhang; Min Lou; Ran Xie; Changlong Jiang (Analytica Chimica Acta, 2026)

The Lactate–lactylation circuitry in kidney fibrosis: cellular crosstalk from tubular metabolic reprogramming to macrophage effector functions - Yiwei Shang; Yunguang Wang; Qikai Luo; Ran He; Shaoting Wang; Binqi Wang; Weiye Lin; Yourou Zhou; Qing He; Qiang He; Juan Jin (Seminars in Immunopathology, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Erratum to “The role of macrophage-myofibroblast transition in the pathogenesis of multi-organ fibrosis” [Tissue Cell 103 (2026) 103702] - Congcong Guo; Ran Cao; Lin Liao; Junyu Zhao; Tianzuo Wang; Junhan Li; Yue Zhang; Haotian Li (Tissue and Cell, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Radio frequency-enhanced remediation of PAHs-contaminated soils using peroxydisulfate: Performance and mechanistic insights - Wenhao Qi; Anxu Sheng; Dawei Lan; Zezhou Zhao; Yao Shi; Fengjiao Zhang; Jiang Lin; Ying Ran; Wei Lou; Jing Chen; Xiaohui Wu; Linling Wang (Journal of Environmental Management, 2026)

Epigallocatechin gallate attenuates free fatty acid-induced hepatocyte apoptosis by restoring endoplasmic reticulum homeostasis - Ran Yu; Yunlong Jiang; Shujing Tan; Junpeng Huang; Dong Hu; Lin Zhou; Muhammad Huraira Waseem; Weiguo Zhao; Chengmin Li (Veterinary Research Communications, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

Tuning electron transfer and surface dual-sites for synergistic peroxymonosulfate activation toward efficient 2,4,6‑trichlorophenol degradation - Jingyi Wang; Yitong Liu; Wenhui Qiu; Lin Zhang; Kaige Li; Ran Wang; Bo Cao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Hydraulic performance of circular tunnels with interior drainage boundaries subjected to water level fluctuation - Hao-Ran Lai; Dong-Mei Zhang; Yi-Yao Shen; Bin-Lin Gan (Transportation Geotechnics, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

A ternary reaction triggering fluorescence/colorimetric dual-mode signals for visual detection of ammonium nitrogen in environmental samples - Xuelian Zhang; Jie Cao; Yingying Liu; Fei Lin; Min Lou; Ran Xie; Changlong Jiang (Journal of Hazardous Materials, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Revealing thermoelectric property-performance correlations for the design of self-powered sensors - Zijian Lin; Bangzhou Tian; Xiaobo Tan; Chuke Zhao; Jiaxing Luo; Zhilong Zhao; Fan Feng; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2026)

Hyaluronic acid-based supramolecular peptide-drug conjugate prodrug nanosystems for precise multiple myeloma therapy - Xiangyu Deng; Qili Huang; Li Cao; Ran Luo; Wenyan Wang; Hongzhong Chen; Chendi Ding; Lina Su; Lin Mei (Carbohydrate Polymers, 2026)

Linking dissolved organic matter sources to greenhouse gas potential in thermokarst lakes of the Qinghai–Tibet Plateau - Wenyan Liu; Zeyong Gao; Chengming Zhang; Fujun Niu; Yibo Wang; Zhanju Lin; Youhua Ran; Jing Luo; Guoan Yin; Yunhu Shang (Cold Regions Science and Technology, 2026)

Levels and emission factors of polycyclic aromatic hydrocarbons in night market cooking fumes - Thi-Hieu Le; Cindy Soo Yun Tan; Hsin-Chieh Kung; Riza P. Gumaling; Danielle E. Que; How-Ran Chao; Ying I. Tsai; Xuan-Thanh Bui; Guo-Ping Chang-Chien; Lin-Chi Wang (Atmospheric Environment, 2026)

Regulatory patterns of antibody-dependent cellular phagocytosis–related genes in triple-negative breast cancer: An integrated multi-omics and single-cell analysis - Guihua Hong; Zhanyue Cui; Xiaowen Xu; Shiwei Lin; Changqing Yang; Ran Ding; Ludan Liang; Ying Chen; Ziyue Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Revealing uncertainties of on-road emissions in a mountainous city using multi-source data - Zeyu Zhang; Qiuzi Chen; Weizhen Lin; Ran Tu; Wenyu Wang; Xiaotong Zhang; An Wang (Transportation Research Part D: Transport and Environment, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

An intelligent multi-stage fishway integrating computer vision and adaptive hydraulic control - Guiwen Rong; Tengyu Ma; Hongling Jiang; Shangzhi Chen; Yangyan Zhang; Guoqing Zhao; Hai Lin; Huaiqin Ran (Ecological Engineering, 2026)

Paeoniae Radix Alba polysaccharides: Structural characterization, macrophage immunomodulation, and potent vaccine adjuvant activity - Ming Zhao; Yushi Wang; Ran Guan; Shiyue Qin; Guoqiu Li; Jiaqi Wang; Zhiye Wang; Junyan Shang; Lingyi Xu; Qingrui Lin; Yanxia Ding; Xiaodan Ma; et al. (Carbohydrate Polymers, 2026)

Engineering strategies for the biosynthesis of rare sugars in microbial cell factories - Heming Xu; Ran Lu; Mei-Li Sun; Lu Lin; Kaifeng Wang; Xiao-Jun Ji (World Journal of Microbiology and Biotechnology, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Embryonic Proto-Tethys Ocean: Evidence from the early Ediacaran Kuyake ophiolite mélange along the Altyn Tagh in NW China - Hong-Ran Wang; Chuan-Lin Zhang; Hua-Dong Ma; Yan Jing; Masumeh Sargazi; Zhi-Hao Song (Precambrian Research, 2026)

Optimal scheduling of mixed conventional and modular autonomous bus fleets for sustainable urban transit - Xueping Dou; Ran Dong; Yuqi Lin; Tongfei Li (Journal of Cleaner Production, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Effects of baking degree of Longjing green tea on flavor attributes, antioxidant activity and advanced glycation end products - Ran Wei; Xiao-Yu Zhong; Kayama Kayama; Yu-Hong Lin; Fang-Ting Qin; Zhu-Cheng Su; Yong-Quan Xu (Food Research International, 2026)

How do climate change risks affect environmental governance? Evidence from the national level - Xin Yue Song; Chi Wei Su; Ran Tao; Lin Jie Liu (Climatic Change, 2026)

Nondecomposer-mediated nutrient transfer in soils: experimental evidence from Drosophila - Yunchao Luo; Run Liu; Tingting Cao; Jiayue Zhang; Mengna Zhao; Ke Li; Zunian Ran; Lin Wang; Xingjun Tian (Applied Soil Ecology, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

A scalable and efficient framework for city-scale building energy modeling with microclimate considerations - Ke Liu; Xiaodong Xu; Deqing Lin; Ran Zhang; Linzhi Zhao; Abudureheman Abuduwayiti; Francesco Causone (Sustainable Cities and Society, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Enhanced polystyrene nanoplastic removal by CTAB-modified magnetic biochar: Adsorption performance and mechanisms - Longwei Fu; Ruili Gao; Bin Xue; Ran Duan; Kun Ma; Lin Chen; Biao Jia (Journal of Environmental Management, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Tailored V/Mn/Ti ratio unlocks high-performance phosphate cathodes for sodium-ion batteries - Zhanhao Zhang; Xingjie Shao; Junjie Fan; Zhiyong Xiong; Yonglin Huo; Lei Ran; Hongcheng Lu; Wanxiu Xiao; Xitao lin; Hongdong Liu; Maowen Xu (Chemical Engineering Journal, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Removal of Mg2+ and Al3+ from high-concentration wet-process phosphoric acid by NH4MgAlF6 complexation-precipitation - Ran Zhu; Zili Wang; Yangyang Luo; E. Yang; Shisong Yang; Qian Lin; Hongyan Pan; Zheng Chen (Journal of Environmental Chemical Engineering, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

Insights into the binding mechanism of Monascus pigment with Holo-ovotransferrin by multispectral and molecular dynamics simulation - Yan Fan; Xi-Yuan Guan; Can-Huan Liang; Jia-Lin Chen; Si-Ran Zhang; Sheng Huang; Qin Wang; Wen-Hua Yang (Food Chemistry, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Alkali promotion in nonmetallic boron-based catalysts: Establishing structure–activity correlations for selective methane oxidation - Ran Yan; Penghui Li; Siyu Liu; Xindi Zhang; Leisu Li; Chenxin Zhang; Shaolong Wan; Jingdong Lin; Xiaodong Yi; Lingtao Liu; Shuai Wang (Chemical Engineering Journal, 2026)

Unraveling the critical role of nanoplastics in governing the interfacial behavior and toxicity evolution of ciprofloxacin during Fenton oxidation process - Hanjun Zhu; Haishuai Cui; Guopei Huang; Hai Yang; Jukun Xiong; Meimei Ran; Xiaoping Lin; Quan Wan; Lele Yang; Zelin Xu; Xin Nie (Chemical Engineering Journal, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Contribution of herbaceous energy crops in maintaining runoff and reducing soil loss on the loess slopes under natural rainfall in the semi-arid area - Ran Huai; Lingchao Meng; Tianni Cheng; Yingge Xie; Yulei Ma; Zhihua Shi; Gao-Lin Wu (CATENA, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Early Cretaceous shortening event recorded by the emplacement of the Tiantai pluton, Eastern South China Block - Ran An; Wei Wei; Wei Lin; Chao Song; Yang Chu (Tectonophysics, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Zero-valent iron induced redox oscillations: Mechanisms of dynamic Fe(II) promote ferrihydrite transformation and lattice immobilization for Pb, Cd, and As - Zhi Jiang; HongZhen Ran; Lin Yu; PengWei Zhao; Weichun Yang (Chemical Engineering Journal, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Constructing an integrated photocatalytic-Fenton-like system for rapid sterilization by S-scheme SCN@CuS heterojunction with manipulated charge dynamics and activated H2O2 - Mingzhu Yuan; Ran Qiu; Weile Xie; Yan Ke; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Qinghua Liu; Xiangang Lin (Chemical Engineering Journal, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

Regulation of sub-Tg solid-state surface crosslinking of reactive polyarylene ether substrate into loose nanofiltration membranes for dyes desalination - Libo Hao; Junni Xie; Lin Pan; Xingbao Yang; Qimeng Ran; Fengfan Gong; Gaolei Zhan; Dongsheng Wang; Xiaobo Liu; Kun Jia (Water Research, 2025)

Quasi-individual-level analysis of urban green space accessibility: Disparities, determinants, and equity across neighborhoods - Chenyu Fang; Mei-Po Kwan; Lin Zhou; Ran Chen; Xing Liu; Shidong Ge (Urban Forestry & Urban Greening, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Enhanced degradation of sulfamethazine by Achromobacter via oxygenation through co-metabolism - Luping Zeng; Xianke Lin; Hongwei Du; Huaiyang Fang; Xiuqin Tan; Bangjie Huang; Yang Yang; Ran Tao (Journal of Environmental Management, 2025)

Br-doped BiOIO3 for efficient and stable photocatalytic oxidation of elemental mercury - Ran Chen; Haoyu Jiang; Jiang Wu; Bin Chen; Zhou Shi; Huanan Wang; Le Chen; Jili Wen; Jia Lin; Yang Ling (Journal of Environmental Chemical Engineering, 2025)

Harvesting low−grade heat by architecting the hierarchical porous structure of green delignified corn husk for solar−driven seawater desalination - Saqib Mehmood; Wang Jianquan; Jinlong Jiang; Chengwei Lin; Yanlong Shang; Du Ran (Journal of Environmental Chemical Engineering, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Elucidation of Pt-Co synergistic effects in Pt30-Co50@WNxC1−x/W electrodes via operando DRT for enhanced HER kinetics - Yinquan Zhang; Hui Song; Tianjiao Lou; Wenqing Liu; Chunxia Lin; Jiangwen Xu; Guangshun Ran; Jinxu Song; Yukun Chang; Hongyi Li; Jinshu Wang (Chemical Engineering Journal, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Evaluation of Human Settlement Quality of Nyingchi City, Southeastern Qinghai-Tibet Plateau, China - Feng Lin; Zhongbao Xin; Lishan Ran; Junxi Qian (Chinese Geographical Science, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Oxidative stress and inflammation in renal fibrosis: Novel molecular mechanisms and therapeutic targets - Haojie Liu; Xiadan Xiang; Chengqian Shi; Jiaowei Guo; Ting Ran; Jinglian Lin; Futing Dong; Jie Yang; Hua Miao (Chemico-Biological Interactions, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

A comprehensive perspective on intestinal health, physiological status, and growth performance of Larimichthys crocea with different stocking densities in recirculating aquaculture systems - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture International, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Dissolved organic matter-mediated photosensitized activation of peracetic acid for micropollutant abatement in wastewater effluent - Hailin Wen; Chuanjing Lin; Chii Shang; Senhao Lu; Zijun Dong; Jingyun Fang; Ran Yin (Journal of Hazardous Materials, 2025)

Simultaneous doping of anions and cations to construct an internal electric field to promote photocatalytic activity - Tongtong Guan; Ran Chen; Yijun Wu; Xiantuo Chen; Jili Wen; Huanan Wang; Le Chen; Yingsu Qu; Mengyuan Hu; Jiang Wu; Jia Lin (Journal of Environmental Chemical Engineering, 2025)

One-step baking soda activation induces N, S-self-doped Ginkgo biloba-derived carbon for efficient chlorine removal - Jiaxi Wang; Limei Sun; Shuaishuai Zhang; Yao Zhang; Ran Zhang; Lin Tian; Yan Xu; Ming Song; Wenchang Zhuang; Wenyi Tan (Journal of Environmental Chemical Engineering, 2025)

Biomass carbon sphere supported structure ZnWO4@C catalyst generates superoxide radicals for efficient oxidative desulfurization of oils - Yifei Zhou; Chunfeng Mao; Ran Wu; Menghua Li; Guangqiang Lin; Zihao Zhang (Journal of Environmental Chemical Engineering, 2025)

Millennial-scale episodic coral growth on the northern margin of the South China Sea - Yuyang Lin; Tian-ran Chen; Nicole D. Leonard; Jian-xin Zhao (Global and Planetary Change, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Core-tailored carbon dots with ultrabroadband dynamic afterglow for highly secure data encryption and anticounterfeiting - Yatao Pan; Xiangbo Ding; Lin Cai; Zhongran Wei; Shihong Wang; Zhanpeng Liu; Xia Ran; Lijun Guo (Chemical Engineering Journal, 2025)

Electrostatic-modulated assembly of charged COF nanosheets into high-performance nanofiltration-based desalination membranes - Shan Luo; Ran Chen; Ruiyuan Zeng; Dai Shi; Youqing Tian; Jiamei Sun; Zifan Song; Yuanhui Xiao; Jiashu Yuan; Jianghuan Shi; Haixiong Liu; Hanyang Liu; et al. (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Interannual Variability of Wintertime Marine Cold Air Outbreaks over the High-Latitude North Atlantic - Huanhuan Ran; Lin Wang; Thomas Spengler (Journal of Meteorological Research, 2025)

Adaptive evolution, expression, and functional analysis of Hyou1 gene in response to hypoxic stress in razor clam (Sinonovacula constricta) - Ran Sun; Zhihua Lin; Hanhan Yao; Liyuan Lv; Yinghui Dong (Aquaculture International, 2025)

Observational Study of Local and Non-local Effects on Aerosols Vertical Distribution in the Boundary Layers - Haijiong Sun; Lin Wang; Hongrong Shi; Liang Ran; Jinqiang Zhang; Zhixuan Bai; Bai Liu; Xiaoqiong Zhen; Xuehua Fan; Hongbin Chen (Aerosol Science and Engineering, 2025)

Effects of exercise intensity on large yellow croaker (Larimichthys crocea): A comprehensive analysis of growth, physiology, muscle fiber structure, and gut health - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Jie Ding; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture, 2025)

Study on the oil supply characteristics of R290 rotary compressors under high-speed conditions - Jie Lin; Ran Zhang; Che Wang; Jianhua Wu; Liangyou Zhu (International Journal of Refrigeration, 2025)

Unveiling the differences between vitexin and isovitexin: From the perspective of sources, green advanced extraction technologies, biological activities, and safety - Jinquan Lin; Hao Ran; Qiqian Feng; Qun Shen; Sumei Zhou; Yuanlin Sun; Dianzhi Hou (Food Chemistry, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Structural optimization and mechanical property analysis of butterfly valves based on Kriging surrogate model - Lei Shi; Tao Yang; JiangYan Ma; Lin Huang; Ao Tian; Yang Xuan; Yan Tian; Ran Gao (Building and Environment, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Mineralization interaction process between an air bubble and carbon or ash particles collected from coal gasification fine slag - Ruifeng Chen; Hainan Wang; Bin Lin; Danlong Li; Bolong Zhang; Jincai Ran; Haijun Zhang (Fuel, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

LAMB3 regulates extracellular matrix stiffness and promotes odontoblast differentiation in dental papilla - Jiangyi Wang; Qiong Li; Xiaoyu Lin; Lei Hu; Wenwen Guo; Ran Zhang; Jinsong Wang; Chunmei Zhang; Songlin Wang; Xiaoshan Wu (Chemical Engineering Journal, 2025)

In situ implantable and reactive oxygen species responsive hydrogel loaded with minocycline for functional rehabilitation of traumatic brain injury - Jie Zhou; Yuanyuan Ran; Chenye Qiao; Jingjing Liang; Yufei Wang; Wei Su; Yonghao Xiao; Lin Ye; Jianing Xi; Zongjian Liu (Chemical Engineering Journal, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

The Association of Blood Cobalt Levels with Cardiovascular and Chronic Kidney Diseases: Mediating Role of Inflammatory Indicators (SII, NLR, PLR, NMLR, and LMR) - Bei-Bei Lu; Qian Luo; Xiao-Lin Yuan; Qing-Song Chen; Jing-Yang Ran; Xing-Wei Zhe; Xiao-Hui Liao (Cardiovascular Toxicology, 2025)

Efficient mining of natural products from Mangrove streptomyces using NP-PRESS - Lin Yu; Junxiao Wang; Kai Jin; Fan Xu; Yi Huang; Ran Zhang; Yihan Wu; Fei Xu (Archives of Microbiology, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Air flow field Testing, simulation and Optimization of CO2 air-source heat pump outdoor unit arrays - Li Xiaoyu; Shi Lin; Ma Li; Xu We; Wang Tiansheng; Zheng Siyu; Tian Ran; Yuan Jing; Cui Yujia (Energy and Buildings, 2025)

MCPA-Na exposure in aquatic systems: disruption of pathways and increased susceptibility to infection in fish - Yanxia Lin; Ran Shi; Mengzhen Wang; Yali Wang; Yunfan Han; Yongcui Ma; Liyin Li; Xiaohua Xia (Aquatic Toxicology, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Pillar[5]arene@AuNP-Functionalized, Magnetically-Propelled Helical Micromotors for On-The-Fly Electrochemical Biosensing of p53 DNA Sequence - Zhiyong Ran; Yue Li; Xiankun Lin; Qiang He (Chemical Engineering Journal, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Slow-release ferrous effects on synchronous stabilization of lead, cadmium, and arsenic in soil - Zhi Jiang; HongZhen Ran; Lin Yu; Mei Jiang; Weichun Yang (Environmental Geochemistry and Health, 2025)

The composite edible film of sodium alginate and natamycin maintained color of pedicel and calyx of tomato fruit - Lin Zhangyao; Liu Hu; Yan Ran; Chen Qingmin; Fu Maorun; Xin Xiaofei (Postharvest Biology and Technology, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Interpretable data-driven urban building energy modeling considering inter-building effect - Deqing Lin; Xiaodong Xu; Ke Liu; Tingjin Wu; Xi Wang; Ran Zhang (Building and Environment, 2025)

Crop domestication increased photosynthetic phosphorus-use efficiency associated with changes in leaf phosphorus fractions under low soil phosphorus conditions - Cai Wang; Lin-Wei Xu; Qiu-Xia Ran; Jiayin Pang; Hans Lambers; Jin He (Plant and Soil, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Analysis of tripartite evolutionary game for maritime supply chain collaboration considering carbon emission governance - Lequn Zhu; Ran Zhou; Xiaojun Li; Lin Zheng (Frontiers in Marine Science, 2025)
The maritime supply chain is undergoing a significant transformation as the industry converges on a consensus to promote low-carbon and sustainable development. In response, governments and international organizations have implemented and updated policies to establish greenhouse gas (GHG) emission targets for the shipping industry. Achieving green and low-carbon sustainable development in the maritime supply chain necessitates coordinated decision-making among three primary entities: governments, shipping companies, and port enterprises. In this paper, a combination of system dynamics (SD) and evolutionary game theory is employed to examine the decision-making behaviors of these three parties and analyze their evolutionary pathways. Data on recent investments by typical enterprises and government subsidies have been collected, and an SD model is utilized to empirically verify the overall evolutionary process of the system and conduct a sensitivity analysis. Our findings indicate that the intensity and stability of government regulatory policies are pivotal in driving the low-carbon transformation of the maritime supply chain. Notably, a nonlinear relationship is observed between the severity of government policies and enterprise decisions. Furthermore, the level of collaboration between port and shipping enterprises in selecting technological pathways directly impacts the effectiveness of emission reductions. Additionally, the extent of low-carbon preference in market demand significantly influences the effectiveness of policies and the strategic choices made by enterprises.

Loss of KIFC1 activity induces spindle instability and actin defects during porcine oocyte maturation - Yu-Ran Wang; Peng-Jie Wang; Le-Yan Tao; Lin-Lin Hu; Qiang-Qiang Liu; Shao-Chen Sun; Jing-Xi Wei; Yue Wang (Theriogenology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Assessing the Impacts of the Israeli–Palestinian Conflict on Global Sea Transportation: From the View of Mass Tanker Trajectories - Bing Zhang; Xiaohui Chen; Haiyan Liu; Lin Ye; Ran Zhang; Yunpeng Zhao (Journal of Marine Science and Engineering, 2025)
Sea transportation plays a vital role in global trade, and studying the impact of emergencies on global sea transportation is essential to ensure the stability of trade. At present, the conflict between Palestine and Israel has attracted extensive attention worldwide. However, there is a lack of specific research on the impact of conflict on shipping, particularly on global shipping costs. By using the global vessel trajectory data of tankers from the Automatic Identification System (AIS) and taking the global sea transportation of large tankers as an example, this paper quantifies and visualizes the changes in global sea transportation before and after conflicts from a data-driven perspective. Firstly, the complete vessel trajectory, as well as the port of departure and the port of destination are extracted. Then, from the perspective of shipping cost and vessel traffic flow, we evaluate the vessel traffic flow changes caused by the conflict by using the route distance to replace the shipping costs and quantify the cost increase for the relevant countries caused by the vessel detour based on the shipping cost increment index. The research results show that after the outbreak of the conflict, the number of vessels passing through the Red Sea area has decreased significantly. About 3.1% of global vessels were affected, with global sea transportation costs of large tankers increasing by about 0.0825%. This study takes the Israeli–Palestinian conflict as an example and analyzes the impact of emergencies on the global sea transportation situation of tankers based on AIS data. The research results reveal the characteristics of international shipping to a certain extent and provide guidance for global sea transportation route planning.

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Transcriptome analysis reveals the dynamics of gene expression during early embryonic development of hybrid groupers - Fengying Yan; Chongwei Wang; Yuzhi Zhu; Jinhui Wu; JiayuYang; Songyong Gan; Hao Ran Lin; Yong Zhang; Shuisheng Li (Aquaculture, 2025)

Comprehensive analysis of flow-induced vibration and rotation characteristics of near-wall hydrofoil - Lin Ding; Yiran Duan; Xiangxi Mao; Jingyu Ran (Ocean Engineering, 2025)

AIS data-driven analysis for identifying cargo handling events in international trade tankers - Ran Zhang; Daozhu Dong; Xiaohui Chen; Bing Zhang; Yixuan Zhang; Lin Ye; Bing Liu; Ying Zhao; Chunyan Peng (Ocean Engineering, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

Comprehensive suitability assessment of fish habitat by integrating mechanism model and bayesian network model - Yuliang Yuan; Ran Li; Jingjie Feng; Hang Wan; Honghui Lin; Xiaolong Cheng (Ecological Engineering, 2025)

High yield production of L-isoleucine through readjusting the ratio of two direct precursors in Escherichia coli - Congrong Shi; Xiaojing Huo; Ran You; Yong Tao; Baixue Lin (Bioresource Technology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Three-dimensional Finite-Element Forward Modeling and Response Characteristic Analysis of Multifrequency Electromagnetic - Jun Zhou; Ke He; Zhi-yan Liu; Shuai Ruan; Hong-lin Ran (Applied Geophysics, 2025)

Identification and hazard prioritization of hydrophobic organic chemicals in flowback and produced water particles: Implications for water management - Huiju Lin; Cheng Zhong; Ran Wen; Tsz Hin Ma; Ding He; Jonathan W. Martin; Greg G. Goss; Daniel S. Alessi; Yuhe He (Water Research, 2025)

Enhanced priming effect in agricultural soils driven by high-quality exogenous organic carbon additions: A meta-analysis - Yuyao Zhang; Hongyu Hu; Yiguo Ran; Ping Huang; Yunlong Cai; Lin Chen; Congzhi Zhang; Xin Gao; Donghao Ma; Jiabao Zhang (Science of The Total Environment, 2025)

Review of vibration induced by gas-liquid two-phase flow inside pipes - Lin Ding; Yitong Fu; Xiang Li; Jingyu Ran (Ocean Engineering, 2025)

Magnetic polydopamine nanoparticles as stabilisers for enzyme-Pickering emulsions: Application in the interfacial catalytic reaction of olive oil - Ziqi Lin; Linhua Huang; Adil Mohamed Abker; Deog-Hwan Oh; Jihan Mohamed Kassem; Mohamed Salama; Ran Shi; Xing Fu (Food Chemistry, 2025)

Cascade energy transfer endows phosphorescent carbon dots-based films with tunable and broadband afterglow for fingerprint recognition and anticounterfeiting - Zhanpeng Liu; Xiangbo Ding; Lin Cai; Yihan Jia; Xia Ran; Zhongzheng Guo; Dan Mo; Yatao Pan; Lijun Guo (Chemical Engineering Journal, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Vessel Type Recognition Using a Multi-Graph Fusion Method Integrating Vessel Trajectory Sequence and Dependency Relations - Lin Ye; Xiaohui Chen; Haiyan Liu; Ran Zhang; Bing Zhang; Yunpeng Zhao; Dewei Zhou (Journal of Marine Science and Engineering, 2024)
In the field of research into vessel type recognition utilizing trajectory data, researchers have primarily concentrated on developing models based on trajectory sequences to extract the relevant information. However, this approach often overlooks the crucial significance of the spatial dependency relationships among trajectory points, posing challenges for comprehensively capturing the intricate features of vessel travel patterns. To address this limitation, our study introduces a novel multi-graph fusion representation method that integrates both trajectory sequences and dependency relationships to optimize the task of vessel type recognition. The proposed method initially extracts the spatiotemporal features and behavioral semantic features from vessel trajectories. By utilizing these behavioral semantic features, the key nodes within the trajectory that exhibit dependencies are identified. Subsequently, graph structures are constructed to represent the intricate dependencies between these nodes and the sequences of trajectory points. These graph structures are then processed through graph convolutional networks (GCNs), which integrate various sources of information within the graphs to obtain behavioral representations of vessel trajectories. Finally, these representations are applied to the task of vessel type recognition for experimental validation. The experimental results indicate that this method significantly enhances vessel type recognition performance when compared to other baseline methods. Additionally, ablation experiments have been conducted to validate the effectiveness of each component of the method. This innovative approach not only delves deeply into the behavioral representations of vessel trajectories but also contributes to advancements in intelligent water traffic control.

Targeting modulation of intestinal flora through oral route by an antimicrobial nucleic acid-loaded exosome-like nanovesicles to improve Parkinson’s disease - Weitong Cui; Zhiyong Guo; Xingyu Chen; Ran Yan; Wenjuan Ma; Xiao Yang; Yunfeng Lin (Science Bulletin, 2024)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

New insights into uranium biomineralization mediated by Pseudomonas sp. WG2-6 in the presence of organic phosphorus: Promoting effect of extracellular polymeric substance and formation of U-P nanominerals - Lin Zhou; Siyu Hou; XingQi Duan; Yalin Lu; Jiali Liao; Ning Liu; Ran Zhao; Changsong Zhao (Journal of Hazardous Materials, 2024)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage - Shan-Shan Jiang; Hao-Ran Lv; Hui-Min Lin; Jie Feng; Soottawat Benjakul; Shucheng Liu; Bin Zhang (Food Bioscience, 2024)

Fe (hydr)oxides and organic colloids mediate colloid-bound chromium mobilization in Cr(VI) contaminated paddy soil - Ting Liu; Ran Wei; Jingjing Li; Weipeng Xie; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Environmental Pollution, 2024)

Investigating carbon peak prediction scenarios and implementation strategies in higher education institutions: A case study of Shandong Jianzhu university - Qianmiao Yang; Lan Wang; Ran Huo; Weihua Lin; Xiaofeng Li (Energy and Buildings, 2024)

Peroxymonosulfate-based electrochemical advanced oxidation for pollutant degradation: Roles of Co-phase regulation and electro-induced polarized particle electrodes - Yunlong Liu; Ran Hao; Zhenyu Shi; Wei Zhang; Can Jin; Liang Zhu; Chunmei Tang; Guifeng Liu; Shuping Huo; Lin Xu; Zhenwu Kong (Chemical Engineering Journal, 2024)

Screening and identification of photoresponse factors in kiwifruit (Actinidia arguta) development - Hailei Huang; Miaomiao Lin; Leiming Sun; Ran Wang; Yukuo Li; Xiujuan Qi (Molecular Biology Reports, 2024)

Near-surface turbulent dissipation at a laboratory-scale confluence: implications on gas transfer - Saiyu Yuan; Jiawei Lin; Hongwu Tang; Yunqiang Zhu; Qihua Ran; George Constantinescu; Carlo Gualtieri (Environmental Fluid Mechanics, 2024)
River confluences contribute to the outflux of saturated dissolved gases in the water resulting from high dam discharges. This process is related to gas transfer across the water–air interface, which is primarily controlled by turbulent dissipation near the water surface. However, the near-surface turbulence dissipation is rarely reported in confluence hydrodynamics studies. This study conducted experiments with different discharge ratios to investigate near-surface turbulent motions at a laboratory-scale confluence. The higher dissipation rate $$ε H/U_{m}^{3}$$ ε H / U m 3 of near-surface turbulence was mainly located inside the interfacial shear layer between the two incoming streams (~ 10 –4 ) and the bank separation zone (10 –4 –10 –3 ) where high shear was found in the mean flow. By contrast, the dissipation rates were much lower inside the incoming flows and outside the two regions of high shear (~ 10 –5 ). The magnitudes of the dissipation rate inside the shear layer were comparable in experiments where the mixing interface was in the Kelvin–Helmholtz mode or in the wake mode. The dissipation rate was found to increase away from the free surface outside the shear layer, while it was more uniformly distributed over the depth inside the layer possibly due to the presence of strongly-coherent, vertically-orientated vortices. In the far field, the mean shear within the shear layer was largely weakened. Nonetheless, the effects of flow separation persisted and laterally expanded to occupy the entire cross section. The dissipation rate $$ε H/U_{m}^{3}$$ ε H / U m 3 of the confluent flow was more than 10 –4 even at a distance of 10 times the channel width in the post-confluence channel.

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

An adaptive trajectory segmentation and simplification algorithm based on vessel behavioral features - Lin Ye; Xiaohui Chen; Ran Zhang; Bing Zhang; Haiyan Liu (Ocean Engineering, 2024)

Half substitution of mineral N with fish protein hydrolysate enhancing microbial residue C and N storage and climate benefits under high straw residue return - Jia Lin Wang; Xin Yu Liu; Pei Kun Jiang; Qiu Ran Yu; Qiu Fang Xu (Journal of Environmental Management, 2024)

Dissect the association between per- and polyfluoroalkyl substances (PFAS) and kidney function from the perspective of lipid molecules - Yi-Ran Chen; Shao-Bin Lin; Jia-Yun Lv; Yan Wu; Wen-Ru Feng (Environmental Pollution, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

A reverse tracing of the water flow path algorithm for slope length extraction based on triangulated irregular network - Zhiyu Lin; Jianliang Xie; Yao Tang; Jianghua Ran; Yongbin Tan (Computers & Geosciences, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

The effect of dietary full-fat Hermetia illucens larvae meal on growth performance and intestine physiology in largemouth bass (Micropterus salmoides) - Wenjing Dong; Xvdong Ran; Guanglun He; Wei Hu; Yongjun Chen; Yuanfa He; Shimei Lin (Animal Feed Science and Technology, 2024)

White matter microstructure damage measured by automated fiber quantification correlates with pain symptoms in lung cancer patients - Li Ran; Jiang Liu; Xiaosong Lan; Xiaoyu Zhou; Yong Tan; Jing Zhang; Yu Tang; Lin Tang; Jiuquan Zhang; Daihong Liu (Brain Imaging and Behavior, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protocatechuic acid enhanced Fe(III) activated peroxymonosulfate system for Sulfamethoxazole degradation in groundwater - Siqi Wang; Ran Wang; Qiutong Lin; Ruixin Liu; Xiaoyu Wu; Guangshan Zhang; Qi Hu; Zhao Jiang; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Pathogenesis-Related Protein 10 Family Genes Involved in Sugarcane Responses to Biotic Stressors and Salicylic Acid - Liang-Nian Xu; Xia-Ran Jiang; Jia-Xin Lin; Juan Li; Talha Javed; Jian-Ying Zhao; San-Ji Gao (Journal of Plant Growth Regulation, 2024)

DNA demethylase Tet2 promotes the terminal maturation of natural killer cells - Yuqing Lin; Biyun Yang; Hailin Liu; Guanghe Ran; Liang Song; Meng Meng; Xiaofeng Yin; Qinghua Bi; Dongmei Yan; Youcai Deng; Yonghui Lu (Immunologic Research, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

A down-regulated cytochrome P450 in Neoseiulus barkeri Hughes (Acari: Phytoseiidae) can dechlorinate and hydroxylate chlorpyrifos without producing chlorpyrifos-oxon - Shi-Jiang Yu; Li Wang; Li-Li Ding; Qi Pan; Si-Chen Li; Liu Liu; Lin Cong; Chun Ran (Journal of Hazardous Materials, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

Modulating ferroptosis for the prevention of urinary stone recurrence: An innovative strategy employing Tetrahedral Framework Nucleic acids and Polydatin conjugates - Shijian Feng; Ran Yan; Cai Tang; Zhaofa Yin; Bohan Liu; Pengan Chen; Yushi He; Liang Zhou; Yunfeng Lin (Chemical Engineering Journal, 2024)

Autophagy aggravates multi-walled carbon nanotube-induced ferroptosis by suppressing PGC-1 dependent-mitochondrial biogenesis in lung epithelial cells - Lin Zhu; Deyu Zhu; Jiahui Ran; Maojie Li; Zhebin Lai; Yan Zhou; Lei Luo; Xiliang Liu; Kanmin Mao; Kunming Tian (Chemico-Biological Interactions, 2024)

Analyzing fishery data and exploring the resource status of Antarctic krill based on its environmental dependence - Rui Wang; Shigang Liu; Ran Zhang; Hai Li; Puqing Song; Yuan Li; Longshan Lin (Fisheries Oceanography, 2024)
Antarctic krill Euphausia superba is a key species in the Southern Ocean ecosystem and has important ecological value. It is also one of the main fishery resources in the Southern Ocean with high economic value. In recent years, with the development of krill fishery and rapid climate change, the conservation and management of krill resources have faced unprecedented challenges. The krill resource is different from the general fishery resources. Due to the krill schooling characteristics, fishery data has some advantages over scientific survey data. Reviewing and analyzing the krill fishery data is necessary. Therefore, in this study, four fishery resource indices (FRIs) were calculated based on Antarctic krill fishery data, and based on the environmental dependence of Antarctic krill, the FRI with the strongest environmental dependence was screened by using the Gradient Forest Model, and the step changes of the FRI with strongest environmental dependence was examined by using the sequential t‐test analyses of regime shifts (STARS). The generalized additive model (GAM) to analyze the correlation between the FRI with the strongest environmental dependence and the main environmental factors, and then explore the resource status of Antarctic krill in the study area. The model results showed that the “FRI_hual” had the strongest environmental dependence and was a better indicator of the status of the Antarctic krill in the study area than the others. In the 2009–2010 year, “FRI_hual” had an obvious regime shift. The interaction of environmental factors “ice_area_2” and “SSH_1” has a great impact on “FRI_hual”. Methods used and results obtained in the study can provide new ideas and a scientific reference for future work, including integrated stock assessment of krill and krill resource monitoring, conservation, and management based on the ecosystem.

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Energy-economy-environment assessment of key feedstock production for ternary lithium-ion batteries via hydrometallurgical recycling and natural exploitation - Kai Wang; Quanshui Huang; Ran Feng; Shaojun Liu; Peng Xing; Zi-Tao Yu; Qingyang Lin; Xiang Gao (Journal of Cleaner Production, 2024)

Assessing the modulation of outer bank erosion by slump blocks: A case study from Marqu Meadow, China - Lei Liu; Lekui Zhu; Dong Chen; Qihua Ran; Honglei Tang; Jun Yan; Lin Liu (Geomorphology, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

Amelioration of radiation cystitis by tetrahedral framework nucleic acid nanostructures functionalized with quercetin - Wei Wang; Ran Yan; Lede Lin; Liao Peng; Yang Xiong; Huiling Chen; Xiaoshuai Gao; Kun Liu; Liang Zhou; Yunfeng Lin (Chemical Engineering Journal, 2024)

Formation of secondary aerosol by 222 nm Far-UVC irradiation on SO2 - Zhancong Liang; Liyuan Zhou; Kunpeng Chen; Ying-Hsuan Lin; Alvin C.K. Lai; Patrick K.H. Lee; Patrick H.L. Sit; Ran Yin; Chak K. Chan (Atmospheric Environment, 2024)

Dose–response relationship between arsenic in drinking water and mortality of urinary cancers in Taiwan - Ya-Ling Chung; Ming-Hsien Lin; Yung-Po Liaw; How-Ran Guo (Environmental Geochemistry and Health, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Neuroprotective and vasoprotective effects of herb pair of Zhiqiao-Danggui in ischemic stroke uncovered by LC-MS/MS-based metabolomics approach - Benxing Yao; Di Xu; Qing Wang; Lin Liu; Ziyun Hu; Wenya Liu; Qi Zheng; Huihui Meng; Ran Xiao; Qian Xu; Yudie Hu; Junsong Wang (Metabolic Brain Disease, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

A comparative study on hydrocarbon detection using cepstrum–based methods - Cong Tang; Kang Chen; Qing-Lin He; Long Wen; Qi Ran; Bin Luo; Jing-Hui Chang; Ya-Juan Xue (Journal of Applied Geophysics, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Meta-analysis addressing the potential of antibiotic resistance gene elimination through aerobic composting - Hongge Wang; Xuan Wang; Lu Zhang; Xinyuan Zhang; Yubo Cao; Ran Xiao; Zhaohai Bai; Lin Ma (Waste Management, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

The role of C18 fatty acids in improving the digestion and retrogradation properties of highland barley starch - Mengzi Nie; Jiaxin Li; Ran Lin; Xue Gong; Bin Dang; Wengang Zhang; Xijuan Yang; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Gas-to-particle partitioning of atmospheric water-soluble organic aerosols: Indications from high-resolution observations of stable carbon isotope - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Xiao-Ying Yang; Tian Xie; Yu-Xian Zhang; Yongwen Xue (Atmospheric Environment, 2024)

Systemic evaluation of novel acaricide hexythiazox for bioactivity improvement and risk reduction at the enantiomer level - Ping Zhang; Furong Yang; Lulu Ran; Cancan Yang; Can Tang; Xiaojiang Ke; Juanni Chen; Wei Xiao; Lin He; Zhifeng Xu (Science of The Total Environment, 2024)

A review on geological storage of marine carbon dioxide: Challenges and prospects - Jinzhou Zhao; Jianchao Zheng; Lan Ren; Ran Lin; Bo Zhou (Marine and Petroleum Geology, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Isolation, identification and whole-genome analysis of an Achromobacter strain with a novel sulfamethazine resistance gene and sulfamethazine degradation gene cluster - Luping Zeng; Hongwei Du; Xianke Lin; Ruomei Liao; Ying Man; Huaiyang Fang; Yang Yang; Ran Tao (Bioresource Technology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Ecoregion-wise fractional mapping of tree functional composition in temperate mixed forests with sentinel data: Integrating time-series spectral and radar data - Ziyu Lin; K.H. Cheng; Dedi Yang; Fei Xu; Guangqin Song; Ran Meng; Jing Wang; Xiaolin Zhu; Michael Ng; Jin Wu (Remote Sensing of Environment, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Occurrence of Cladosporium herbarum causing leaf spot on Avena sativa in China - Jiangui Zhang; Guiqin Zhao; Jikuan Chai; Liang Zeng; Wenlong Gong; Fu Ran; Xiumei Nie; Ruifang Zhang; Doudou Lin (Crop Protection, 2024)

Petrogenesis of the late Cenozoic potassium-rich volcanism in the NW Tibetan Plateau: Constraints on the mantle evolution through post-orogenic events - Masumeh Sargazi; Chuan-Lin Zhang; Zhi-Hao Song; Hong-Ran Wang; Zahid Hussain; Xian-Tao Ye; Wei Wang; Xiao-Fei Du (Lithos, 2024)

A versatile AIE probe with two cross-talk-free emissions for dual detection of SO2 and viscosity and its application in food and biological imaging - Di Zhang; Min Wang; Man Li; Lin Liu; Ran Duan; Nana Xue; He Chen; Lijun Shang; Tieliang Wang; Xujin Wu; Junfeng Zhang (Food Chemistry, 2024)

Defect-promoted nanoparticles−nanorod Ni−NiMoO4 heterogeneous nanostructures as efficient electrocatalysts to overall water/urea splitting in fresh/sea water - Caihong Fang; Ran Li; Xin Wang; Fei Duan; Junfeng Lin; Yunqin Hu; Zhiqing Cui (Chemical Engineering Journal, 2024)

Micro- and nano-hybrid cellulose fibers prepared by straightforward and high-efficiency hot water soaking-assisted colloid grinding for high-performance cellulose paper - Huiping Lin; Guolong Hong; Mingen Fei; Yiqin Shen; Xinxiang Zhang; Jian Li; Wenbin Yang; Ran Li (Carbohydrate Polymers, 2024)

Roles and sources of B vitamins in the marine ecosystem - Lin Wang; Hancheng Zhao; Ran Bi; Xiaohan Chen; Zhendong Lyu; Wenhua Liu (Reviews in Fish Biology and Fisheries, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Progress and evolution of hotspots in butterfly diversity research in green spaces - Ying Lin; Shanjun Huang; Wenqiang Fang; Shiyuan Fan; Chengyu Ran; Emily Dang; Weicong Fu; Zhipeng Zhu (Environmental Science and Pollution Research, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

Production of carbon nanotubes via catalytic pyrolysis of polyethylene over Ni/ZSM-5 prepared by ethylene glycol assisted impregnation - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Tao-li Huhe; Hao-Ran Yuan; Yong Chen (Fuel, 2024)

Deeply analyzing dynamic fermentation of highland barley vinegar: Main physicochemical factors, key flavors, and dominate microorganisms - Yan Li; Aixia Wang; Bin Dang; Xijuan Yang; Mengzi Nie; Zhiying Chen; Ran Lin; Lili Wang; Fengzhong Wang; Li-Tao Tong (Food Research International, 2024)

Groundwater Quality and Vulnerability Assessment in a Semiarid Karst Region of Northern China - Ran An; Shu Wang; Zongjun Gao; Zhenyan Wang; Wei Li; Qijun Deng; Lü Lin; Yuanqing Liu (Journal of Earth Science, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Contrasting lake changes in Tibet revealed by recent multi-modal satellite observations - Jiangjun Ran; Lin Liu; Guoqing Zhang; C.K. Shum; Jiahui Qiu; Ruigang Hu; Jianping Li; Junhuan Peng; Cheinway Hwang; Yi Luan; Yue Sun; Min Xu; et al. (Science of The Total Environment, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Cyclic Impact Damage and Water Saturation Effects on Mechanical Properties and Kaiser Effect of Red Sandstone Under Uniaxial Cyclic Loading and Unloading Compression - Kui Zhao; Lin Zhang; Daoxue Yang; Jiefang Jin; Peng Zeng; Xing Wang; Shanhu Ran; Dongming Deng (Rock Mechanics and Rock Engineering, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Exploring the potential of magnetic persimmon tannins-based bio-adsorbent for Cd (II) ions removal from water: Experiment and DFT study - Fan Zhou; Lin Gao; Shunyan Cui; Jing Tian; Tong Wang; Guiyin Li; Zhongmin Wang; Chaoke Qin; Dahong Lin; Weijiang Gan; Zhaojin Ran (Journal of Water Process Engineering, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

An electroconductive hydrogel with injectable and self-healing properties accelerates peripheral nerve regeneration and motor functional recovery - Zhenwei Yi; Fangke Zhan; Yijia Chen; Ran Zhang; Haodong Lin; Liming Zhao (Chemical Engineering Journal, 2023)

A Comparative Analysis of Three Rutaceae Species Reveals the Multilayered Mechanisms of Citrus in Response to Huanglongbing Disease - Yunuo Liu; Liting Dong; Danlu Ran; Shuai Wang; Rongrong Qu; Lin Zheng; Aihong Peng; Yongrui He; Shanchun Chen; Xiuping Zou (Journal of Plant Growth Regulation, 2023)

Spatial distribution and migration of lead and zinc and the influence of parent materials in typical paddy soils of Hunan Province, China - Yi-fan Xiang; Da-juan Wan; Chen-ran Wang; Jun-lin Huang; Xue-ying Cao; Jia-qi Chen; Ning-xiang Ouyang (Environmental Monitoring and Assessment, 2023)

Review on in situ Isotopic Analysis by LA-MC-ICP-MS - Jie Lin; Ao Yang; Ran Lin; Ji Mao; Zhaochu Hu; Yongsheng Liu (Journal of Earth Science, 2023)

Effects of different Solanum sect. Solanum (Solanaceae) straw amendments on selenium accumulation and growth of grapevine - Kewen Huang; Xu Chen; Ran Zhang; Yiping Dong; Qunxian Deng; Yan Huang; Lei Liu; Ting Wang; Ming’an Liao; Lijin Lin (Acta Physiologiae Plantarum, 2023)

First pelagic fish biodiversity assessment of Cosmonaut Sea based on environmental DNA - Yuzhuo Liao; Xing Miao; Rui Wang; Ran Zhang; Hai Li; Longshan Lin (Marine Environmental Research, 2023)

A machine-learning assisted multi-cluster assessment for decarbonization in the chemical fiber industry toward net-zero: A case study in a Chinese province - Ran Feng; Xu Xu; Zi-Tao Yu; Qingyang Lin (Journal of Cleaner Production, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

From rainfall to runoff: The role of soil moisture in a mountainous catchment - Sheng Ye; Lin Liu; Jiyu Li; Hailong Pan; Wei Li; Qihua Ran (Journal of Hydrology, 2023)

Deep transfer learning based on transformer for flood forecasting in data-sparse basins - Yuanhao Xu; Kairong Lin; Caihong Hu; Shuli Wang; Qiang Wu; Li Zhang; Guang Ran (Journal of Hydrology, 2023)

Ambient air pollution associated with incident asthma, subsequent cardiovascular disease and death: A trajectory analysis of a national cohort - Xiaojie Wang; Shanshan Ran; Hui Xia; Hui Shi; Gan Wu; Zilong Zhang; Chongjian Wang; Miao Cai; Junguo Zhang; Hualiang Lin (Journal of Hazardous Materials, 2023)

Urchin-like fluorinated covalent organic frameworks decorated fabric for effective self-cleaning and versatile oil/water separation - Yixin Yang; Jinghan Dong; Ran Wang; Zian Lin; Zongwei Cai (Journal of Hazardous Materials, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Fabrication of bimetallic MOF with 2D nanosheets structure and rich active sites for enhanced removal of organic pollutants by activation of peroxymonosulfate - Ning Li; Huanxuan Li; Ran Ji; Sihang Lin; Chen Xu; Jingang Huang; Qingwei Zhou; Shuguang Lyu; Feng Li; Junhong Tang (Journal of Environmental Chemical Engineering, 2023)

Synergistic enhanced activation of peroxymonosulfate by heterojunction Co3O4–CuO@CN for removal of oxytetracycline: Performance, mechanism, and stability - Ning Li; Huanxuan Li; Chen Xu; Zhong Zhou; Tao Rao; Ran Ji; Sihang Lin; Jia Du; Shaodan Xu; Shuguang Lyu; Feng Li; Junhong Tang (Environmental Research, 2023)

Evolution stage identification of haze pollution episodes in beijing using constrained dynamic time warping and multiway principal component analysis - Hao Zhang; Yilun Lin; Jinye Ran; Junyi Yu; Morui Zhu; Hengqi Li; Yongli Jiao (Environmental Modelling & Software, 2023)

Fabrication of organic P-N aerogel towards simultaneously super thermal insulation, enhanced compressive strength, flame retardancy and smoke suppression for the rigid polyurethane foam - Ying-Ming Li; Wen-Juan Hu; Shuang-Lin Hu; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

The effect of chlorogenic acid, a potential botanical insecticide, on gene transcription and protein expression of carboxylesterases in the armyworm (Mythimna separata) - Dong-jiang Lin; Ya-xin Zhang; Yong Fang; San-ji Gao; Ran Wang; Jin-da Wang (Pesticide Biochemistry and Physiology, 2023)

Inactivation of fungal spores by performic acid in water: Comparisons with peracetic acid - Yuzhao Lin; Xiangqian Xu; Shiqi Tian; Jingyi Wang; Shumiao Cao; Tinglin Huang; Weiping Xie; Zhilin Ran; Gang Wen (Journal of Hazardous Materials, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

Experimental and numerical study on 2-DOF wind-induced vibration and energy harvesting of triangular prism - Qunfeng Zou; Lin Ding; Tian Song; Jingyu Ran; Li Zhang (Ocean Engineering, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Kinetic modelling of the mass and heat transfer of a plant-based fishball alternative during deep-fat frying and air frying and the changes in physicochemical properties - Xinli Ran; Dingsong Lin; Lingjie Zheng; Yifan Li; Hongshun Yang (Journal of Food Engineering, 2023)

Strategic tillage is a promising alternative to conventional and no-tillage: Evidence from a 12-year field trial in a double-cropped rice system - Xing Wang; Cong He; Bai-Jian Lin; Xin Zhao; Ran Zhang; Ling-Tao Zhong; Xiao-Ping Xiao; Hai-Lin Zhang (European Journal of Agronomy, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Major genomic mutations driving hepatocellular carcinoma - Ran Chen; Moubin Lin; Daming Gao (Genome Instability & Disease, 2023)

Legacy and novel perfluoroalkyl substances in major economic species of invertebrates in South China Sea: Health implication from consumption - Jieyi Diao; Zhenwei Chen; Chuanghong Su; Jianwen Wang; Zhixin Zheng; Qiongping Sun; Lin Wang; Ran Bi; Tieyu Wang (Marine Pollution Bulletin, 2023)

Comparison of machine learning models for performance evaluation of wind-induced vibration piezoelectric energy harvester with fin-shaped attachments - Tian Song; Lin Ding; Lin Yang; Jingyu Ran; Li Zhang (Ocean Engineering, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Field investigation on the change process of microbial community structure in large-deep reservoir during the initial impoundment - Sizhen Liang; Fangbo Zhang; Ran Li; Hailong Sun; Jingjie Feng; Zhuo Chen; Honghui Lin (Journal of Environmental Management, 2023)

The influences of the oil circulation ratio on the performance of a vapor injection scroll compressor in heat pump air conditioning system intended for electrical vehicles - Kang Li; Jingru Ma; Jian Cao; Bin Zhang; Binlin Dou; Ni Liu; Hua Zhang; Lin Su; Xuejin Zhou; Ran Tu (International Journal of Refrigeration, 2023)

Carbon nanotubes production from catalytic pyrolysis of polyethylene over nickel-based catalysts: The influence of support materials - Qing-Lin Li; Rui Shan; Shu-Xiao Wang; Hao-Ran Yuan; Yong Chen (Fuel, 2023)

Differences in the diversity and community structure of the intestinal microbiota of commercial fishes in the central and southern East China Sea in spring and autumn - Jiali Xiang; Shigang Liu; Puqing Song; Ran Zhang; Yuan Li; Longshan Lin (Environmental Biology of Fishes, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Consistent differences in brain structure and functional connectivity in high-altitude native Tibetans and immigrants - Xinjuan Zhang; Weiwei Xie; Wenrui Du; Yanqiu Liu; Jianzhong Lin; Wu Yin; Lihui Yang; Fengjuan Yuan; Ran Zhang; Haipeng Liu; Hailin Ma; Jiaxing Zhang (Brain Imaging and Behavior, 2023)

Chemical decontamination of foods using non-thermal plasma-activated water - Samuel Herianto; Rachelle D. Arcega; Chih-Yao Hou; How-Ran Chao; Ching-Chang Lee; Chia-Min Lin; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2023)

Multifunctional injectable hydrogel promotes functional recovery after stroke by modulating microglial polarization, angiogenesis and neuroplasticity - Xiaoyu Ma; Fuhai Gao; Wei Su; Yuanyuan Ran; Tuerhong Bilalijiang; Yerasel Tuolhen; Guiqin Tian; Lin Ye; Zengguo Feng; Jianing Xi; Zongjian Liu (Chemical Engineering Journal, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Targeting autophagy receptors OPTN and SQSTM1 as a novel therapeutic strategy for osteoporosis complicated with Alzheimer's disease - Ran Duan; Chun-Gu Hong; Meng-Lu Chen; Xin Wang; Zhi-Lin Pang; Hui Xie; Zheng-Zhao Liu (Chemico-Biological Interactions, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Effects of light on growth, feeding rate, digestion, and antioxidation in juvenile razor clams Sinonovacula constricta - Mengqi Zhang; Fei Kong; Bin Ma; Deshui Chen; Zhaoshou Ran; Shuonan Ma; Kai Liao; Jiayi Cao; Lin Zhang; Xiaojun Yan; Jilin Xu (Aquaculture, 2023)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Human umbilical cord mesenchymal stem cell-derived exosomes carrying miR-1827 downregulate SUCNR1 to inhibit macrophage M2 polarization and prevent colorectal liver metastasis - Jierong Chen; Ziyue Li; Caifeng Yue; Jianhong Ma; Lixue Cao; Jiaxin Lin; Dandan Zhu; Ran An; Jinxin Lai; Yunmiao Guo; Bing Gu (Apoptosis, 2023)

Insights into the promotion of urine-diverting toilets based on the fertilizer efficiency of artificial phosphate ore recovered from source-separated urine - Yuan Liu; Qi Zhang; Lin-Feng He; Yang Ran; Ying-Ying Deng; Hong Liu (Resources, Conservation and Recycling, 2023)

Lipid transformation during postmortem chilled aging in Mongolian sheep using lipidomics - Min Zhang; Rina Su; Mirco Corazzin; Ran Hou; Yue Zhang; Lina Sun; Guanhua Hu; Lu Dou; Yueying Guo; Lin Su; Lihua Zhao; Ye Jin (Food Chemistry, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Effects of Vertical Water Column Temperature on Distribution of Juvenile Tuna Species in the South China Sea - Shigang Liu; Yuan Li; Rui Wang; Xing Miao; Ran Zhang; Siyuan Chen; Puqing Song; Longshan Lin (Fishes, 2023)
In this study, we conducted two surveys in the central and southern parts of the South China Sea, in autumn 2012 and spring 2013. Six juvenile tuna species were caught in each survey. Gradient forest analysis (GFA) and a generalized additive model (GAM) were used to analyze the relationship between the catch per unit effort (CPUE) for the juvenile tuna species and six sea temperature indices for the South China Sea. In the GFA, the temperature difference between the sea surface and 50 m depth (D50) showed the highest importance to CPUE than other indices, which indicates that D50 was the best predictor of the abundance of juvenile tuna species. The GAM analysis showed that lower deep-water temperature, a shallow mixed layer depth, and a higher difference in temperature between the surface and deeper water were associated with increased CPUE. The results indicate that a relatively rapid decrease in vertical water temperature is favorable for the aggregation of juvenile tuna. These results contribute to understanding of the distribution mechanism of juvenile tuna species in the South China Sea and provide a scientific basis for the rational development and utilization of tuna resources.

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

CH4 and CO2 emissions in water networks of rice cultivation regions - Ouping Deng; Jiangyou Ran; Xuesong Gao; Xiangjun Lin; Ting Lan; Ling Luo; Yalan Xiong; Jiang Liu; Dinghua Ou; Jianbo Fei; Rong Huang (Environmental Research, 2023)

Transcriptome and DNA Methylation Responses in the Liver of Yellowfin Seabream Under Starvation Stress - Yi Long Lin; Zong Xian Zhu; Chun Hui Ai; Ying Ying Xiong; Tong De Liu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Biochar regulates enzymes activity and interspecies electron transfer to promote bioenergy recovery from a continuous two-stage food waste anaerobic digestion process - Tugui Yuan; Ran Sun; Mingshuai Shao; Qindong Chen; Yeqi Lin; Qiyong Xu (Journal of Cleaner Production, 2023)

Impacts of hydraulic conditions on microplastics biofilm development, shear stresses distribution, and microbial community structures in drinking water distribution pipes - Xiao Chen; Xiao-ying Lian; Yi Wang; Sheng Chen; Yi-ran Sun; Guo-lin Tao; Qiao-wen Tan; Jing-chun Feng (Journal of Environmental Management, 2023)

Hollow Co-CeO2@PEG nanospheres: Ultrasound enhanced cascade-nanozyme for synergetic anticancer - Miao Wang; Stephen Choi; Qingchen Bai; Kai Yu; Wei Guo; Feng Zhang; Ran Jia; Fengyu Qu; Huiming Lin (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

Incineration disposal of organic waste bio-residue via a deep dewatering process using refuse incineration bottom ash: moisture transfer and low calorific value improvement - Ran Wei; Ruina Zhang; Lijie Song; Xiong Zhou; Shunhong Lin; Youcai Zhao; Tao Zhou (Environmental Science and Pollution Research, 2022)

Extracellular histones induce inflammation and senescence of vascular smooth muscle cells by activating the AMPK/FOXO4 signaling pathway - Hang Yang; Yong-Yan Luo; Lue-Tao Zhang; Kai-Ran He; Xiao-Jun Lin (Inflammation Research, 2022)

Underestimation of biogenic silica sinking flux due to dissolution in sediment traps: A case study in the South China Sea - Wen Liang; Lihua Ran; Zhi Yang; Martin G. Wiesner; Yuzhao Liang; Lin Sun; Jianfang Chen (Frontiers in Marine Science, 2022)
The dissolved silicate concentrations in the supernatant of sediment trap sampling bottles retrieved from deep water (1000-3000 m) at four stations in the South China Sea (SCS) were measured to calculate the underestimated flux of biogenic silica (bSi) in sinking particles due to bSi dissolution. High dissolved silicate concentrations in the supernatant, ranging from 122.6 to 1365.8 μmol/L, indicated significant dissolution of particulate bSi in the sampling bottles. Underestimation of the bSi flux in the SCS by ~2% to ~34% (average: ~10%) due to bSi dissolution was revealed, and the degree of underestimation increased with decreasing total bSi flux. The amount of bSi dissolved within the sampling series at each station was generally positively correlated with dissolution time and to a certain extent influenced by the bSi amount collected by the sampling bottles under a low bSi sinking flux. Apparently stronger bSi dissolution was found at two of the four stations due to relatively high bSi dissolution rates, which were possibly related to a higher reactive surface area of the bSi or bacterial activity. Overall, our results demonstrated that the considerable bSi dissolution in sediment trap sampling bottles should not be ignored, especially in the low-productivity oligotrophic ocean, and bSi flux calibration via measurement of the dissolved silicate in sampling bottles is necessary. To reduce bSi flux underestimation due to the deployment of time-series sediment traps, larger-volume sampling bottles should be avoided in the oligotrophic open ocean, and sinking particle samples should be analyzed as soon as the sediment traps are recovered.

DNA barcoding provides insights into Fish Diversity and Molecular Taxonomy of the Amundsen Sea - Shuai Cao; Yuan Li; Xing Miao; Ran Zhang; Longshan Lin; Hai Li (Conservation Genetics Resources, 2022)

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Diagnostic Performance of miR-485-3p in Patients with Parkinson’s Disease and its Relationship with Neuroinflammation - Xia Lin; Rui Wang; Ran Li; Taotao Tao; Danhong Zhang; Yuxiang Qi (NeuroMolecular Medicine, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

Research on Transfer Rate of Heavy Metals and Harmful Elements in Traditional Chinese Medicine Extraction and Refining Processes and Product Health Risk Assessment - Dujia Jin; Lin Li; Wujun Dong; Xiangyang Zhu; Xuejun Xia; Renyun Wang; Jun Ye; Ran Li; Zhihua Liu; Xueqing Xu; Lili Gao; Yuling Liu; et al. (Biological Trace Element Research, 2022)

Glacier lanternfish (Benthosema glaciale) first found on the continental slope of the Pacific Arctic - Ran Zhang; Yuan Li; Qiaohong Liu; Puqing Song; Hai Li; Rui Wang; Shaoxiong Ding; Longshan Lin (Polar Biology, 2022)

Demersal fish diversity and molecular taxonomy in the Bering Sea and Chukchi Sea - Hai Li; Fang Yang; Xuehua Wang; Yuan Li; Nan Zhang; Ran Zhang; Cheng Liu; Hushun Zhang; Longshan Lin; Puqing Song (Conservation Genetics Resources, 2022)

Spatio-temporal characteristics of demersal fish community in the Chukchi and northern Bering Seas: significant distributional records and interannual variations in species composition and biodiversity - Ran Zhang; Puqing Song; Hai Li; Rui Wang; Yuan Li; Xing Miao; Longshan Lin; Shaoxiong Ding (Polar Biology, 2022)

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Evaluation and improvement of the greenness of plasma spraying through life cycle assessment and grey relational analysis - Jing Liu; Liming Wang; Fangyi Li; Yanle Li; Xueju Ran; Lin Kong; Yan Fu (The International Journal of Life Cycle Assessment, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Adsorptive Removal of Low-Concentration Cr(VI) in Aqueous Solution by Mg–Al Layered Double Oxides - Lin Fan; Bo Zhou; Sheng Zhang; Sihai Hu; Xiaohui Mi; Ran Sun; Yaoguo Wu (Bulletin of Environmental Contamination and Toxicology, 2021)

Urbanization and carbon emission: causality evidence from the new industrialized economies - Khalid Khan; Chi-Wei Su; Ran Tao; Lin-Na Hao (Environment, Development and Sustainability, 2020)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Roles of MicroRNA-122 in Cardiovascular Fibrosis and Related Diseases - Ying Liu; Jia-Wei Song; Jian-Yu Lin; Ran Miao; Jiu-Chang Zhong (Cardiovascular Toxicology, 2020)

The correlation analyses of bacterial community composition and spatial factors between freshwater and sediment in Poyang Lake wetland by using artificial neural network (ANN) modeling - Ran Sun; Zuxin Tu; Lin Fan; Zixia Qiao; Xiaoyan Liu; Sihai Hu; Guohua Zheng; Yaoguo Wu; Ruiwu Wang; Xiaohui Mi (Brazilian Journal of Microbiology, 2020)

Evaluation of freezing tolerance in Actinidia germplasm based on relative electrolyte leakage - Shihang Sun; Xiujuan Qi; Ran Wang; Miaomiao Lin; Jinbao Fang (Horticulture, Environment, and Biotechnology, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Grenville-age orogenic event along the northeastern margin of the Quanji massif, NW China: constraints from ~1.1 Ga migmatite - Zhouxuan Xiao; Licheng Ma; Wan Jiang; Ran Wang; Yuyan Yao; Jie Cai; Jingyu Lin; Lu Li (Geosciences Journal, 2020)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Grass carp (Ctenopharyngodon idella) Bcl-xl: transcriptional regulation and anti-apoptosis analysis - Guoqin Qi; Ningli Yu; Kang Xu; Xiaofen Xie; Yuexin Mao; Xin Chen; Xiaoqin Ran; Xingxing Chen; Gang Lin; Chengyu Hu (Fish Physiology and Biochemistry, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

De Novo and Inherited SETD1A Variants in Early-onset Epilepsy - Xiuya Yu; Lin Yang; Jin Li; Wanxing Li; Dongzhi Li; Ran Wang; Kai Wu; Wenhao Chen; Yi Zhang; Zilong Qiu; Wenhao Zhou (Neuroscience Bulletin, 2019)

Automated Detection of Vulnerable Plaque for Intravascular Optical Coherence Tomography Images - Ran Liu; Yanzhen Zhang; Yangting Zheng; Yaqiong Liu; Yang Zhao; Lin Yi (Cardiovascular Engineering and Technology, 2019)

Population genetic structure of Thryssa kammalensis in the Chinese Seas inferred from control region sequences - Jing Zhang; Nan Zhang; Yuan Li; Jiaguang Xiao; Ran Zhang; Tianxiang Gao; Longshan Lin (Marine Biodiversity, 2019)

Carbon-based magnetic nanocomposite as catalyst for persulfate activation: a critical review - Ya Pang; Kun Luo; Lin Tang; Xue Li; Jiangfang Yu; Junyuan Guo; Yuanyuan Liu; Zhu Zhang; Ran Yue; Ling Li (Environmental Science and Pollution Research, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Theoretical evaluation of group delay on pseudorange bias - Yuqi Liu; Lin Chen; Yi Yang; Hongchen Pan; Yihang Ran (GPS Solutions, 2019)

QTL Mapping for Red Blotches in Malaysia Red Tilapia (Oreochromis spp.) - Bi Jun Li; Zong Xian Zhu; Xiao Hui Gu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Complete genome sequences of three novel cycloviruses identified in a dragonfly (Odonata: Anisoptera) from China - Saif Ul Islam; Wenzhong Lin; Ran Wu; Chen Lin; Waqar Islam; Muhammad Arif; Zhenguo Du; Zujian Wu (Archives of Virology, 2018)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Fish diversity and molecular taxonomy in the Prydz Bay during the 29th CHINARE - Yuan Li; Liyan Zhang; Puqing Song; Ran Zhang; Liangming Wang; Longshan Lin (Acta Oceanologica Sinica, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Performance of GPS and GPS/SINS navigation in the CE-5T1 skip re-entry mission - Meng Wang; Tao Shan; Lin Ma; Ran Tao; Chunliang Chen (GPS Solutions, 2018)

Discovery of potent and selective acetylcholinesterase (AChE) inhibitors: acacetin 7- O -methyl ether Mannich base derivatives synthesised from easy access natural product naringin - Hao-ran Liu; Xue Men; Xiao-hui Gao; Lin-bo Liu; Hao-qun Fan; Xin-hua Xia; Qiu-an Wang (Natural Product Research, 2018)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Sources and transformations of nitrogen in the South China Sea: insights from nitrogen isotopes - Zhi Yang; Jianfang Chen; Min Chen; Lihua Ran; Hongliang Li; Peng Lin; Yong Zhu; Chunsheng Wang; Zhongqiang Ji; Jingjing Zhang (Journal of Oceanography, 2018)

Differential Gene Expression Profiles and Alternative Isoform Regulations in Gill of Nile Tilapia in Response to Acute Hypoxia - Hong Lian Li; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Assessment of rhizosphere processes for removing water-borne macrolide antibiotics in constructed wetlands - Yiping Tai; Nora Fung-Yee Tam; Yunv Dai; Yang Yang; Jianhua Lin; Ran Tao; Yufen Yang; Jiaxi Wang; Rui Wang; Wenda Huang; Xiaodan Xu (Plant and Soil, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Association of ulcerative colitis with transcobalamin II gene polymorphisms and serum homocysteine, vitamin B12, and folate levels in Chinese patients - Shuzi Zheng; Wei Yang; Chaoqun Wu; Liang Sun; Daopo Lin; Xiuqing Lin; Lijia Jiang; Ran Ding; Yi Jiang (Immunogenetics, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Modeling and Manufacturing Technology for Personalized Biological Fixed Implants - Zhang Guoqing; Yang Yongqiang; Lin Hui; Song Changhui; Xiao Ran; Yu Jiakuo (Journal of Medical and Biological Engineering, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

C-myc overexpression drives melanoma metastasis by promoting vasculogenic mimicry via c-myc/snail/Bax signaling - Xian Lin; Ran Sun; Xiulan Zhao; Dongwang Zhu; Xueming Zhao; Qiang Gu; Xueyi Dong; Danfang Zhang; Yanhui Zhang; Yanlei Li; Baocun Sun (Journal of Molecular Medicine, 2017)

Cluster spacing optimization of multi-stage fracturing in horizontal shale gas wells based on stimulated reservoir volume evaluation - Ran Lin; Lan Ren; Jinzhou Zhao; Leize Wu; Yuanzhao Li (Arabian Journal of Geosciences, 2017)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

A large stokes-shifted fluorescent dye synthesized as a new probe for the determination of protein - Dayong Lin; Xuening Fei; Ran Li; Yingchun Gu; Yalin Tang; Jianguo Zhou; Baolian Zhang (Journal of Fluorescence, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

New phenyl derivatives from endophytic fungus Botryosphaeria sp. SCSIO KcF6 derived of mangrove plant Kandelia candel - Zhi-ran Ju; Xiaochu Qin; Xiu-ping Lin; Jun-feng Wang; Kumaravel Kaliyaperumal; Yong-qi Tian; Juan Liu; Fen Liu; Zhengchao Tu; Shi-hai Xu; Yonghong Liu (Natural Product Research, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Enhanced hydroxyl radical generation in the combined ozonation and electrolysis process using carbon nanotubes containing gas diffusion cathode - Donghai Wu; Guanghua Lu; Ran Zhang; Qiuhong Lin; Zhenhua Yan; Jianchao Liu; Yi Li (Environmental Science and Pollution Research, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Odontoblast β-catenin signaling regulates fenestration of mouse Hertwig’s epithelial root sheath - Ran Zhang; Yan Teng; Liang Zhu; JingTing Lin; Xiao Yang; Guan Yang; TieJun Li (Science China Life Sciences, 2015)

Spectra, Stability and Labeling of a Novel Carbazole Derivative as a Fluorescent Turn-on DNA Probe - Xuening Fei; Ran Li; Dayong Lin; Yingchun Gu; Lu Yu (Journal of Fluorescence, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Recent Developments and Future Perspectives of Anaerobic Baffled Bioreactor for Wastewater Treatment and Energy Recovery - Gefu Zhu; Ran Zou; Ajay Kumar Jha; Xu Huang; Lin Liu; Chaoxiang Liu (Critical Reviews in Environmental Science and Technology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Ascomycotin A, a new citromycetin analogue produced by Ascomycota sp. Ind19F07 isolated from deep sea sediment - Yong-qi Tian; Xiu-ping Lin; Juan Liu; Kumaravel Kaliyaperumal; Wen Ai; Zhi-ran Ju; Bin Yang; Junfeng Wang; Xian-wen Yang; Yonghong Liu (Natural Product Research, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Effects of manganese deficiency on the microstructure of proximal tibia and OPG/RANKL gene expression in chicks - Ran Liu; Cong Jin; Zhenyong Wang; Zhaojun Wang; Jian Wang; Lin Wang (Veterinary Research Communications, 2015)

Isolation and characterization of 18 microsatellite loci in the Chinese Noctule bat, Nyctalus plancyi - Hao Liu; Yujie Ran; Hongyan Shi; Xiaodong Jia; Lin Zhao (Conservation Genetics Resources, 2015)

Selenium Deficiency Inhibits the Conversion of Thyroidal Thyroxine (T4) to Triiodothyronine (T3) in Chicken Thyroids - Shi-lei Lin; Cong-wu Wang; Si-ran Tan; Yang Liang; Hai-dong Yao; Zi-wei Zhang; Shi-wen Xu (Biological Trace Element Research, 2014)

Effects of organic solvents on two retinal pigment epithelial lipofuscin fluorophores, A2E and all-trans-retinal dimer - Qiu-xia Jin; Xin-ran Dong; Jing-meng Chen; Ke Yao; Ya-lin Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Fine stratigraphic division of volcanic reservoir by uniting of well data and seismic data—Taking volcanic reservoir of member one of Yingcheng Formation in Xudong area of Songliao Basin for an example - Huanqing Chen; Yongle Hu; Jiuqiang Jin; Qiquan Ran; Lin Yan (Journal of Earth Science, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Single nucleotide polymorphisms in the upstream regulatory region alter the expression of myostatin - Wei Hu; Songyu Chen; Ran Zhang; Yushuang Lin (In Vitro Cellular & Developmental Biology - Animal, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Dissipation and Residue Determination of Fluoroglycofen-Ethyl in Soybean and Soil by UPLC-MS–MS - Yue Geng; Ran Jia; Chongjiu Li; Xiaodong Ma; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

NAD(P)H oxidase inhibiting with apocynin improved vascular reactivity in tail-suspended hindlimb unweighting rat - Ran Zhang; Hai-hong Ran; Jin Ma; Yun-gang Bai; Le-jian Lin (Journal of Physiology and Biochemistry, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

Neurodevelopment of Infants with Prenatal Exposure to Polybrominated Diphenyl Ethers - Cherng-Gueih Shy; Huei-Lin Huang; Gou-Ping Chang-Chien; How-Ran Chao; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Three new fatty acids from the roots of Boehmeria nivea (L.) Gaudich and their antifungal activities - Qiong-Ming Xu; Yan-Li Liu; Xiao-Ran Li; Xia Li; Shi-Lin Yang (Natural Product Research, 2011)

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Effects of Tai Chi on adiponectin and glucose homeostasis in individuals with cardiovascular risk factors - Rei-Yeuh Chang; Malcolm Koo; Meng-Ying Ho; Zi-Zi Lin; Zer-Ran Yu; Yen-Fen Lin; Be-Jen Wang (European Journal of Applied Physiology, 2011)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Dual bio-responsive gene delivery via reducible poly(amido amine) and survivin-inducible plasmid DNA - Ran Namgung; Jonathan H. Brumbach; Ji Hoon Jeong; James W. Yockman; Sung Wan Kim; Chao Lin; Zhiyuan Zhong; Jan Feijen; Johan F. J. Engbersen; Won Jong Kim (Biotechnology Letters, 2010)

Molecular characterization and expression of 1-deoxy-d-xylulose 5-phosphate reductoisomerase (DXR) gene from Salvia miltiorrhiza - Xiangming Yan; Lin Zhang; Jing Wang; Pan Liao; Yan Zhang; Ran Zhang; Guoyin Kai (Acta Physiologiae Plantarum, 2009)

Climate variability of cold surge and its impact on the air quality of Taiwan - Chuan-Yao Lin; Shih-Chun Candice Lung; How-Ran Guo; Pei-Chih Wu; Huey-Jen Su (Climatic Change, 2009)

Molecular cloning, characterization and expression analysis of a new gene encoding 3-hydroxy-3-methylglutaryl coenzyme A reductase from Salvia miltiorrhiza - Pan Liao; Wei Zhou; Lin Zhang; Jing Wang; Xiangming Yan; Yan Zhang; Ran Zhang; Li Li; Genyu Zhou; Guoyin Kai (Acta Physiologiae Plantarum, 2009)

Iron contributes to the formation of catechol isoquinolines and oxidative toxicity induced by overdose dopamine in dopaminergic SH-SY5Y cells - Ran Wang; Hong Qing; Xiao-Qian Liu; Xiao-Lin Zheng; Yu-Lin Deng (Neuroscience Bulletin, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Alterations in health examination items and skin symptoms from exposure to ultra-low humidity - Tzu-Chieh Chou; Kuen-Huei Lin; Hamm-Min Sheu; Shih-Bin Su; Chia-Wei Lee; How-Ran Guo; Trong-Neng Wu; Ho-Yuan Chang (International Archives of Occupational and Environmental Health, 2007)

Effects of aromatizable and nonaromatizable androgens on the sex inversion of red-spotted grouper (Epinephelus akaara) - Guang-Li Li; Xiao-Chun Liu; Hao-Ran Lin (Fish Physiology and Biochemistry, 2006)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)

Rat Ghrelin Stimulates GH Release and GH mRNA Expressionin the Pituitary of Orange-spotted Grouper, Epinephelus Coioides - Xueqin Ran; Wensheng Li; Haoran Lin (Fish Physiology and Biochemistry, 2004)

Differential expression of glucose-regulated protein 78 during spermatogenesis - Ran Huo; Ye-fei Zhu; Xiang Ma; Min Lin; Zuo-min Zhou; Jia-hao Sha (Cell and Tissue Research, 2004)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Lack of growth hormone-releasing peptide-6 action on in vivo and in vitro growth hormone secretion in sexually immature grass carp (Ctenopharyngodon idellus) - Dong Xiao; Anderson O.L. Wong; Hao-Ran Lin (Fish Physiology and Biochemistry, 2002)